Twenty Questions for Noël Arnaud - Warren F. Motte Jr. (Studies in 20th & 21st Century Literature, 1986)
Noël Arnaud, the president of the Ouvroir de Litterature Potentielle (Oulipo), discusses that institution's history, its literary aesthetic, and its goals. He offers art assessment of twenty-five years of Oulipian activity, in the course of which he touches upon notions which are crucial to the Oulipo's praxis: the fundamental analogy of mathematics and literature, the role of formal constraint in the literary text, and the mutual complementarity of scholarship in literary history and the practice of innovative literary experimentalism.
Keywords: Noël Arnaud; Ouvroir de Litterature Potentielle; Oulipo; literary aesthetic; mathematics; literature; literary history; literary experimentalism